American women in World War I : they also served - Gavin, Lettie, 1922- (University Press of Colorado, 1997)
"American Women in World War I provides the first comprehensive overview of women's role in the World War I war effort. Through personal interview, and excerpts from diaries, letters, and memoirs, the author relates poignant stories of wartime experiences and provides a unique perspective on the progress of women in military service. Devoting one chapter to each of the nine areas of service, the author interweaves richly detailed personal stories with historical photos and background to create a lively account that captures the heart and spirit of the times."--Provided by publisher
Keywords: World War, 1914-1918 -- Women -- United States.; Women -- United States -- History -- 20th century.; War.; Women.; Women; Armed Conflicts; Physicians, Women -- history; United States; Guerre mondiale, 1914-1918 -- Femmes -- États-Unis.; Femmes -- États-Unis -- Histoire -- 20e siècle.; Guerre.; wars.; armed conflicts.; women (female humans); HISTORY -- Military -- World War I.; HISTORY -- General.; 1900-1999; History